The Unusual Attitudes, Sequestration and Conjugal Disharmony in the Select Novels of Anita Desai - Dr.Evangeline Priscilla.B, Dr.Anu Baisel* (International Journal of Advanced Science and Technology, 2020)
This paper depicts the representation of the Indian Women in Anita Desai’s novel Cry the Peacock. Most of the post-modern Indian women novelists exhibit their feminine consciousness through their writing and finding their feminine identity in their female characters. Women play an important role in the life of men. She devotes as mother, sister, friend, lover and wife. Women novelist brings out the strong women who fight for her own identity in male domination society. Women plays sacrifice roles in some extent at the same time. They find it difficult to adjust with the male chauvinist society. Also, the novelists project the female protagonists as a backbone of their own culture and country. They have the capability of holding the family both physically and emotionally. Three types of women consequences are seen in second generation women writers. The first type of women is hyper sensitive and self- analysing often they deal with mental trauma. The second types of women often fight with themselves. They are fragile. While the third group of women comes out from the nut shells and to fights for their individuality and their concerns. Though they are living in a male-dominated world they adjust with social pressures. Still they are proving their identity and maintaining all the social values in their life.. Anita Desai engages herself in highlighting the female Indian predicament of maintaining self -identity as the predominant theme in her works.